High altitude forest composition diversity and its component in a part of Ganga Chotti and Bedori Hills District Bagh, Azad Jammu and Kashmir, Pakistan - Hussain, Malik; Malik, Nafeesa (Acta Geographica Debrecina Landscape & Environment series, 2012)
The effect of altitude on species diversity and its components was recorded in Ganga Chotti and Bedori Hills District Bagh Azad Jammu and Kashmir during 1999-2000. There were 30 plant communities merged in to four plant associations on the basis of cluster analysis. The highest average species diversity was 2.70 at the base (Alt1700 m) in woodland temperate association. Then the diversity declined. At the top (Altitude 3000 m) species diversity was 1.71, while in monsoon diversity was 2.48 at the base and 1.72 at the top. Average species richness was highest at the base (4.06) then decreased with the increase in altitude. Equitability increases from 1700-3350 m (0.71- 1.07) while at the top it decreases (0.77). Species maturity in winter and monsoon was highest at the base and lowest at the top (3000 m).